The Effect of Supply Chain Agility on Firm Performance - Güner, Hasan Mert; Istanbul Commerce University (Journal of International Trade, Logistics and Law, 2018)
In the current rapidly changing, developing and complicating global world, the companies are constantly in a competition with one another. In this competitive environment, the companies need to use their resources in the most accurate manner in order to survive. Companies gain a competitive advantage by responding to variable customer demands in different markets within the shortest time and at the right time. They can also gain this by concentrating the agility factor in the supply chain. In case of uncertainty, the supply chain must be agile for the companies to gain a competitive advantage. In this study, the effects of agility and technological uncertainty on the performance of the company in the supply chain management are examined. In the research, it has been observed that technological uncertainty affects the supply chain agility and the supply chain agility also affects the performance of the company in a positive way.